Homo Economicus and the Economics of Property Rights: History in Reverse Order - Milonakis, Dimitris; Meramveliotakis, Giorgos (Review of Radical Political Economics, 2013)
This article challenges some fundamental propositions of property rights theory by revealing the inability of new institutional economics to fully grasp the notion of property, as reflected in its narrow and problematic definition of property rights. The concept of property relations is proposed as better suited to capture the social and institutional aspects of property. By reconsidering the case of the Montagnais, originally used by Alchian and Demsetz for illustrative purposes, and drawing on the works of Polanyi and McManus, we show that the historical explanation of the emergence of (private) property rights provided by Alchian and Demsetz is flawed.JEL Codes: D02, D23, P14
Economics
Keywords: civil rights; economics; emergence; historical specificity; homo economicus; human rights; institutional economics; property; property relations; property rights; redistribution